RELEVANSI PENGATURAN MAHAR DAN DAMPAKNYA PADA KEHARMONISAN RUMAH TANGGA MASYARAKAT KONTEMPORER DI KECAMATAN TAMAN PERSPEKTIF MADZHAB SYAFI’I - Muhammad Rifqy Fakhrul Hadi; Zaini, Muhammad Farid; Nelud Darajaatul Aliyah (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The concept of mahar is significant in marriage, representing the honor and dignity of the bride. In the perspective of the Syafi’i school of thought, mahar is seen as a symbol of agreement between the couple to build a harmonious household. This study aims to describe the relevance and impact of mahar on the harmony of contemporary marriages in Taman District. This research uses a qualitative method with a phenomenological approach to interpret in-depth experiences in contemporary society in Taman Subdistrict about the impact of dowry on marital harmony. The data sources in this study are religious leaders, couples who have been married for more than 10 years, and couples who have been married for less than 5 years. Data collection techniques were interviews and literature studies. Data were analyzed and then verified using the triangulation method. The results show that mahar is perceived as a personal right of the wife, a condition for the legitimacy of the marriage, and a symbol of the beginning of a happy marriage. The study also found that the concept of mahar payment varies between older and younger couples in the district, with the amount and timing of payment influenced by factors such as economic class, education, occupation, and family background. The study concludes that the impact of mahar on the harmony of contemporary marriages in Taman District is not significant, as mahar is seen as a symbolic gesture that is valued differently by each individual. Keywords:  Dowry, Harmony, Contemporary, Shafi’i Madhab